2020
DOI: 10.1002/kjm2.12231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anxiety on dental students' noncognitive performance in their first objective structured clinical examination

Abstract: Patient-dentist discourse is a core nonoperational competency in dental education. The skills of querying patients and responding to questions are noncognitive attributes, and their evaluation by the standardized patient objective structured clinical examination (OSCE) is particularly necessary. However, it is not clear whether students' test anxiety affects these attributes. This study aims to examine the relationship between dental students' state-trait anxiety, noncognitive performance, and examination resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…Yakar et al 14 reported that female medical students suffered from anxiety more than males during the COVID‐19 pandemic. Wu et al 26 and Zhao et al 27 also found that Chinese female university students experienced more anxiety than males during the COVID‐19 pandemic. Women are more emotional than men due to physiological differences between men and women, such as genetic sensitivity, hormone, and cortisol levels.…”
Section: Discussionmentioning
confidence: 98%
“…Yakar et al 14 reported that female medical students suffered from anxiety more than males during the COVID‐19 pandemic. Wu et al 26 and Zhao et al 27 also found that Chinese female university students experienced more anxiety than males during the COVID‐19 pandemic. Women are more emotional than men due to physiological differences between men and women, such as genetic sensitivity, hormone, and cortisol levels.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study of 35 countries, that were part of the Organisation for Economic Co-operation and Development, found that the factors that significantly affected academic performance were enjoyment, motivation, test anxiety, and self-efficacy [ 2 ]. Among these factors, it is widely recognised that the student’s levels of anxiety and self-efficacy when taking a skills test affects their skill mastery [ 3 , 4 ]. Nursing students may have higher levels of anxiety than students in other fields [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that OSCE is associated with high levels of stress and anxiety (Wadi et al 2022 :54; Wu et al 2020 :854). In this study, although the number of female students was considerably higher than male students, there were no significant gender differences in terms of perceived stress, perceived factors causing stress and perceived incidence of stress.…”
Section: Discussionmentioning
confidence: 99%